The development and use of a blended, organically based fertiliser on sugar cane in the KwaZulu-Natal Midlands - Tweedale, Darryl Neil (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Agric.Admin.) -- University of Stellenbosch, 1999.